The Implementation of Representation State Transfer (REST) Architecture Academic Information System Integrated in Pandanaran Islamic Senior High School - Muhammad Hambali; Bambang Sugiantoro (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
In the rapid development of technology and the increasing speed of information flow due to globalization, making the role of information is vital and crucial to an educational institution. Institutions of Sunan Pandanaran implement policies of separate education system among male students with female students. This triggered a few problems, especially in the Senior high school of Sunan Pandanaran where researched by the author. The focus of the research is how to implement thearchitecture of Representational State Transfer (REST) on the integrated system academic information between two separate data server so that student academic data can be served easily from two different servers. Through the system resulting from this research, researchers offered easy access to student academic data that can then be recycled by the user into a useful information. The research methodology where used in this research is system development. The steps begin with a preliminary study research,data collection, design models, identifying system requirements and system development methods.At the end, this research produced a integrated academic system information between male school servers with a female school server where implemented using Representational State Transfer architecture. So that student academic data can be presented either to the user in order to be recycled into useful information.